Association between dietary selenium intake and depression in patients with or without stroke: a cross-sectional study - Wu, Shuang; Mei, Zhimin; Gao, Jin; Chai, Songshan (Frontiers in Nutrition, 2025)
BackgroundDepression and stroke are life-threatening diseases with high incidence, research suggests an interaction between dietary selenium and depression and stroke. However, the relationship between dietary selenium and depression has not been adequately studied. Therefore, the purpose of this study was to assess the association between dietary selenium and depression among individuals with or without stroke.MethodsA cross-sectional study was performed using the 2011–2018 National Health and Nutrition Examination Survey dataset (N = 15,018). Logistic regression, interaction effect analysis, and restricted cubic spline analysis were used for statistical analyses.ResultsThe association between dietary selenium intake and prevalence depression differed between the non-stroke and stroke groups. Furthermore, when dietary selenium was converted into a categorical variable, there was evidence of an interaction between stroke status and selenium intake on decreasing the prevalence of depression (p = 0.007). What’s more, the dose–response association between dietary selenium intake and depression indicated various patterns between participants with and without stroke.LimitationsA cross-sectional study cannot be used to infer causal relationships.ConclusionA non-linear relationship was observed in individuals without stroke, characterized by an apparent threshold of approximately 128.4 mcg/d. In contrast, no association was observed between dietary selenium intake and depression in participants with stroke. Further research is necessary to validate the present findings.